Inventario de insectos asociados al cultivo de cacao (Theobroma Cacao L) en una plantación con sistema monocultivo en el cantón Baba, recinto Concepción, provincia de Los Ríos - Abril Campuzano, Juan Alberto (2016)
VIII. SUMMARY This research was conducted from June 10 to September 16, 2015, in the cocoa farm''Voluntad God "Baba Located in Canton, enclosure Concepción owned by Mr. Antonio López. The area has a tropical climate with an average temperature of 25.60 ° C; an annual rainfall of 1761.09 mm; relative humidity of 76% and 804.7 hours of sun-loving annual average. The identification was carried out in the Laboratory of Entomology, Faculty of Agricultural Sciences at the Technical University of Babahoyo located at km 7 of the road Babahoyo - Montalvo, between the geographical coordinates 79 ° 32 'west longitude and 01 ° 49' longitude South; with the height of 8 m.s.n.m. The aim of this study was to identify the insects related to the cultivation of cacao (Theobroma cacao L) in a monoculture system, found on the stem, branches, leaves, flowers and fruit of plants, determine the population levels of insects and develop a reference database of insects related to monoculture national cocoa. As for the experimental design used a descriptive analysis was used. The data were averaged, plotted also Pearson correlations between insect populations became the Margalef diversity indexes were studied, (1951). Based on the results twenty-seven species of which twenty of them are species causing crop damage and beneficial species belonging to the order Neuroptera were recorded. The most significant correlation coefficient was introduced between the towns of Toxoptera aurantii and Solenopsis sp which was 0.88 which showed the same significance to bilateral 0.01 level, which means that both species are directly related, the increasing populations Solenopsis sp also going to be increasing populations Toxoptera aurantii. no significant positive correlation between them was found that populations of Camponotus sp and Pseudococcus citri showed Pearson correlation coefficient of 0.1 was given meaning that increases Pseudococcus citri populations will also increase population Camponotus sp, as far as negative presented no significant correlations occurred between the towns of Atta sp Pseudococcus citri and the correlation coefficient was -0.17 showing that there is an inverse relationship between these populations and that growing one decreases the other. In the analysis of biodiversity below and above areas of low diversity values it was found, but no values were indicated high diversity.